2007
DOI: 10.1590/s1415-47572007000400013
|View full text |Cite
|
Sign up to set email alerts
|

Factor XI deficiency in Indian Bos taurus, Bos indicus, Bos taurus x Bos indicus crossbreds and Bubalus bubalis

Abstract: We investigated the occurrence of Factor XI (FXI) deficiency syndrome in the following Indian dairy animals: Bos taurus Holstein-Friesian and Jersey cattle, Bos indicus Indian cattle breeds, B. taurus x B. indicus crossbreds and the river buffalo Bubalus bubalis. Factor XI deficiency is an autosomal recessive bleeding disorder known to affect Holstein cattle worldwide. A total of 1001 dairy animals, mainly bulls, were genotyped to detect the mutation within exon 12 of the gene encoding for factor XI. Two Holst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…In previous studies (Akyüz & Ertuğrul 2006;2008), BLAD and DUMPS alleles were not found in Turkish native cattle breeds. Similarly, BLAD, DUMPS, CVM and BC carriers were not found in Gir cattle in Brazil (Riberio et al 2000), in Polish dairy cattle in Poland (Kaminski et al 2005), in Brown Swiss bulls in Iran (Norouzy et al 2005), in Charolais, Limousine, Beef Simmental, Blonde d'Aquitaine, Belgian Blue, Aberdeen-Angus and Hereford cattle breeds in Czech Republic (Citek et al 2006) and in Jersey cattle, Indian cattle (Bos indicus) breeds, B. taurus x B. indicus crossbreds and the river buffalo (Bubalus bubalis) cattle in India (Patel et al 2007). All these reports and our findings supported the idea that these genetic disorders are specific to only Holstein cattle worldwide.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies (Akyüz & Ertuğrul 2006;2008), BLAD and DUMPS alleles were not found in Turkish native cattle breeds. Similarly, BLAD, DUMPS, CVM and BC carriers were not found in Gir cattle in Brazil (Riberio et al 2000), in Polish dairy cattle in Poland (Kaminski et al 2005), in Brown Swiss bulls in Iran (Norouzy et al 2005), in Charolais, Limousine, Beef Simmental, Blonde d'Aquitaine, Belgian Blue, Aberdeen-Angus and Hereford cattle breeds in Czech Republic (Citek et al 2006) and in Jersey cattle, Indian cattle (Bos indicus) breeds, B. taurus x B. indicus crossbreds and the river buffalo (Bubalus bubalis) cattle in India (Patel et al 2007). All these reports and our findings supported the idea that these genetic disorders are specific to only Holstein cattle worldwide.…”
Section: Resultsmentioning
confidence: 99%
“…This insertion, composed of an imperfect poly-adenine tract followed duplicated region of the normal coding sequence, introduced a premature stop codon (TAA), which impaired the synthesis of functional protein (Marron et al, 2004). Patel et al (2007) found that carrier individual exhibited two fragments with DNA length 247 bp and 324 bp due to the insertion of 77 base pairs insertion within exon 12 of the FXI gene. In this study, we did not find any cattle carrying this genetic defect.…”
Section: Detection Of Mutation Of Factor XI Deficiency (Fxid)mentioning
confidence: 99%
“…These carriers were identified as heterozygous cows and were healthy clinically (Gurgul et al, 2009). Investigation of FXID syndrom in 1001 heads of Indian dairy cattle showed that two holstein bulls detected as heterozygous for FXID, with carrier frequency of 0.6% (Patel et al, 2007). The carriers frequency of the FXID also detected in Turkey, USA, Republic Czech, Iran, Japan with carrier frequency of 1.80%, 1.20%, 0.36%, 2.91% and 2.50% repectively (Meydan et al, 2010;Marron et al, 2004;Čítek et al, 2008;Gurgul et al, 2009;Ghanem et al, 2005).…”
Section: Detection Of Mutation Of Factor XI Deficiency (Fxid)mentioning
confidence: 99%
See 2 more Smart Citations